Energy Analysis of Hemicellulose Extraction at a Softwood Kraft Pulp Mill - Case Study of Södra Cell Värö - Bood, Jon; Nilsson, Linus (My University, 2013)
The Swedish pulp and paper industry is struggling with lower revenues and high raw material cost. The implementation of biorefinery concepts is not only interesting from a diminishing fossil feedstock perspective but also as a way of creating new revenue streams for the pulp and paper industry. Production of dissolving pulp would be beneficial both due to the higher market price of the pulp but also since the hemicellulose extracted could be upgraded to value-added by-products. The conversion from Kraft to dissolving pulp production has been evaluated in a case study of Södra Cell Värö pulp mill. An energy analysis has been performed with pinch technology and the potentials for steam savings and electricity production have been quantified for different levels of process integration. It has been shown that the softwood Kraft pulp mill at Värö can be converted to a dissolving pulp mill by introducing extraction of hemicelluloses prior to the digestion step. The proposed dissolving pulp plant would not only be self sufficient energy wise but in fact be able to produce both more electricity and excess steam than today. The most rigorous process integration proposed enable 71 MW electricity production as well as a surplus of 38 MW LP steam. A less rigorous option with lower investment cost can maximize the electricity production of the current back pressure turbine to 62 MW (from the current capacity at 51 MW), while leaving 28 MW of LP steam available for use elsewhere. The future saw mill and pellet factory, which is planned to be built close by, will require 20 MW of LP steam which has to be subtracted when assessing the steam surplus. Furthermore there might be an additional demand of LP steam for upgrading the extracted hemicellulose.
Keywords: Energi; Hållbar utveckling; Kemiteknik; Energy; Sustainable Development; Chemical Engineering